Misdiagnosis of scrub typhus as hemorrhagic fever with renal syndrome and potential co-infection of both diseases in patients in Shandong Province, China, 2013-2014. - Xiao-Lan Gu; Rui Qi; Wen-Qian Li; Yong-Jun Jiao; Hao Yu; Xue-Jie Yu (PLoS Neglected Tropical Diseases)
Background Scrub typhus, caused by Orientia tsutsugamushi, an obligate intracellular gram-negative bacterium, along with hemorrhagic fever with renal syndrome (HFRS), caused by hantaviruses, are natural-focus infectious diseases prevalent in Shandong Province, China. Both diseases have similar clinical manifestations in certain disease stages and similar epidemic seasons, which has caused difficulties for physicians in distinguishing them. The aim of this study was to investigate whether misdiagnosis of scrub typhus as HFRS occurred in patients in Shandong Province. Methods Serum samples (N = 112) of clinically suspected HFRS patients from 2013 to 2014 in Shandong Province were analyzed with enzyme-linked immunosorbent assay (ELISA) for antibodies to both hantavirus and Orientia tsutsugamushi. Results ELISA showed that 56.3% (63/112) and 8.0% (9/112) of clinically suspected HFRS patients were IgM antibody positive to hantavirus and O. tsutsugamushi, respectively. Among the hantavirus IgM antibody positive patients, 7.9% (5/63) were also IgM antibody positive to O. tsutsugamushi. Among the hantavirus IgM antibody negative sera, 8.2% (4/49) of sera were positive to O. tsutsugamushi. Conclusions We concluded that some scrub typhus patients were misdiagnosed as HFRS and co-infection of scrub typhus and HFRS might exist in China. Due to the different treatments for scrub typhus and HFRS, physicians should carefully differentiate between scrub typhus and HFRS and consider administering anti-rickettsia antibiotics if treatment for HFRS alone does not work.